Treg functional stability and its responsiveness to the microenvironment. Issue 1 (May 2014) - Barbi, Joseph; Pardoll, Drew; Pan, Fan
Summary: Regulatory T cells (Tregs) prevent autoimmunity and tissue damage resulting from excessive or unnecessary immune activation through their suppressive function. While their importance for proper immune control is undeniable, the stability of the Treg lineage has recently become a controversial topic. Many reports have shown dramatic loss of the signature Treg transcription factor Forkhead box protein 3 (Foxp3) and Treg function under various inflammatory conditions. Other recent studies demonstrate that most Tregs are extremely resilient in their expression of Foxp3 and the retention of suppressive function. While this debate is unlikely to be settled in the immediate future, improved understanding of the considerable heterogeneity within the Foxp3 + Treg population and how Treg subsets respond to ranging environmental cues may be keys to reconciliation. In this review, we discuss the diverse mechanisms responsible for the observed stability or instability of Foxp3 + Treg identity and function. These include transcriptional and epigenetic programs, transcript targeting, and posttranslational modifications that appear responsive to numerous elements of the microenvironment. These mechanisms for Treg functional modulation add to the discussion of Treg stability.